2018
DOI: 10.1177/1938640018766627
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Invasive Fixation Can Decrease Infection Rates in Diabetic and Obese Patients With Severe Ankle Fracture and Syndesmotic Injury

Abstract: Therapeutic, Level III: Retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, with the increased awareness of the tenuous soft tissue envelope and the lack of adequate biology at times, recent authors have advocated for alternative fixation methods to help increase rates of limb salvage. Minimally invasive approaches including percutaneous cannulated screws 12,13 or Minimally Invasive Plate Osteosynthesis (MIPO) 14 have been described as techniques to avoid large surgical incisions and maintain periosteal blood supply. Likewise, the use of intramedullary fixation including locked fibular nailing or tibiotalocalcaneal (TTC) nailing also utilizes smaller incisions and can preserve the soft tissue envelope.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the increased awareness of the tenuous soft tissue envelope and the lack of adequate biology at times, recent authors have advocated for alternative fixation methods to help increase rates of limb salvage. Minimally invasive approaches including percutaneous cannulated screws 12,13 or Minimally Invasive Plate Osteosynthesis (MIPO) 14 have been described as techniques to avoid large surgical incisions and maintain periosteal blood supply. Likewise, the use of intramedullary fixation including locked fibular nailing or tibiotalocalcaneal (TTC) nailing also utilizes smaller incisions and can preserve the soft tissue envelope.…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 19 However, suture-button devices are associated with an increased risk of neurovascular bundle entrapment, infections caused by the fiber wire, and osteomyelitis. 18 Pain and irritation have been found similar in both static and dynamic procedures. The risks and benefits of different surgical approaches must be weighed while determining treatment.…”
Section: Treatment Of Syndesmosis Injurymentioning
confidence: 86%
“…Premature degradation of implants is believed to be responsible for malunion in nearly 26% of cases with high rates of osteolysis and sterile wound sinuses. 18 …”
Section: Treatment Of Syndesmosis Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Two small, retrospective studies found low complication rates of complications after percutaneous fixation of ankle fractures in diabetic patients. 12,13 However, a systemic review found that a cohort of diabetic patients with percutaneously treated ankle fractures had a higher rate of implant breakage or migration compared with those who underwent open treatment. 14 Although not definitive, our data suggest we should anticipate a high complication rate in the surgical treatment of these fractures, regardless of the method of fixation.…”
Section: Discussionmentioning
confidence: 99%